استراتيجية لتوطين الصناعة في محافظة بابل - الجنابي، عبدالزهرة علي; الجنابي، زيد عبدالزهرة علي (جامعة بابل - كلية التربية للعلوم الإنسانية, 2023)
فقدت محافظة بابل خلال العقدين الأخيرين أكثر من (3000) منشأة صناعية، وما يزيد على (20) ألف فرصة عمل في هذا القطاع، فيما توصف المنشآت الكبيرة الرئيسة حاليا بأنها شبه معطلة، هذا على الرغم من امتلاك المحافظة تنوعا ومقدارا جيدا من مقومات النشاط الصناعي وعوامل نجاح توطن معظم فروع الصناعات التحويلية، فضلا عن الحاجة الماسة لمختلف أنواع المنتجات الصناعية التي يتم تطمينها بالاستيراد من الخارج. تتميز المحافظة بإنتاجها الزراعي بشقيه النباتي والحيواني، وهذا الإنتاج يشجع على توطين سلسلة من الصناعات الغذائية والنسيجية المعتمدة على مدخلات محلية، ولضمان نجاح عملية التوطين لابد من بناء مجموعة من الصناعات الخادمة للنشاط الزراعي، وفي المقدمة صناعة المعدات الزراعية الثقيلة والخفيفة بتأهيل مجمع الإسكندرية المتخصص فيها ويلحق به منشآت الصناعة معدات النقل المختلفة، فضلا عن الصناعات الكيمياوية الخادمة للزراعة. ويمكن ضمان نجاح توطين الصناعات النسيجية وتأهيل مصانعها القائمة، وكذلك صناعات السوق من الأثاث الخشبي والمعدني والمعدات الكهربائية المختلفة. يمكن أن يعهد إلى القطاع العام في توطين الصناعات الثقيلة الإنتاجية مثل الهندسية والبتروكيمياوية، أما الصناعات الصغيرة والمتوسطة الاستهلاكية منها فيفضل إناطة مهمة توطينها إلى القطاعية الخاص والمختلط. تقترح الدراسة اعتماد نمطي المجمعات والمدن الصناعية بديلا عن الأنماط القديمة، وإقامة مدينتين صناعيتين إحداها في شمالي المحافظة والثانية في جنوبها، وترحيل الصناعات قليلة التلوث إلى الثانية، وترحيل كل الأنشطة الصناعية من مناطق الأعمال المركزية إلى أطراف المدن، وعدم إقامة صناعات ملوثة في المحافظة مثل تصفية النفط وتوليد الطاقة الكهربائية. تؤكد الدراسة على خلق بيئة استثمارية مناسبة بتطبيق مبدأ النافذة الواحدة، ومحاربة الفساد، وحماية المنتج والمستهلك، وتوفير الطاقة والوقود والمال اللازم لإقامة وتطوير المنشآت الصناعية. During the last two decades, Babylon Province has lost more than(3000)industrial establishments, and more than (20) thousand job opportunities in this sector, while the main large establishments are described as almost semi idle, despite the fact that the province possesses a variety and a good amount of the elements of industrial activity, and success factors of localize most of the branches of the manufacturing industries, in addition to the urgent need for various types of industrial products that are reassuring to be imported from abroad. The province is characterized by its agricultural production, both plant and animal, and this production encourages the localization of a series of food and textile industries based on local inputs, then in order to success insurance localization process should built collection factories which serving agriculture such as heavy and light agriculture equipment’s, as well as chemical industries. It is possible to ensure the success of localizing the textile industries and rehabilitating their existing factories, as well as the market industries of wooden and metal furniture and various electrical equipment. The public sector can be entrusted with the localization of heavy productive industries such as engineering and petrochemicals. As for the small and medium consumer industries, it is preferable to entrust the task of localizing them to the private and mixed sectors. The study suggests adopting two types of industrial estates and cities as a substitute for the old types, establishing two industrial cities, one in the north of the governorate and the other in the south, transferring low-pollution industries to the second, transferring all industrial activities from the Central Business District to the outskirts of the cities, and not establishing polluting industries in the governorate such as liquidation oil and electricity generation. The study emphasizes creating an appropriate investment environment by applying the single window principle, fighting corruption, protecting producers and consumers, and providing energy, fuel and money needed to establish and develop industrial facilities.
Keywords: الصناعات التحويلية -- الأنشطة الاقتصادية -- التوطن الصناعي -- الإمكانات الجغرافية